MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAMS ACHIVEMENT DIVISION (STAD) PADA MATA PELAJARAN IPS SISWA KELAS IX H DI MTsN BARABAI KABUPATEN HULU SUNGAI TENGAH TAHUN PELAJARAN 2014/2015 - Anna Hartati (Universitas Lambung Mangkurat, 2014)
The purpose of this study is for improving learning process of social studies in order to increase the completeness of student learning result in social studies. This study designed by using qualitative approach and the kind of this study is classroom action research. This research implemented through four phase, namely: planning, implementation, observation, and reflection. Research subject is class IX H students of MTsN Barabai in first semester year 2014/ 2015. The result of study shown that learning result in first cycle of the average values obtained 68.9 with the number of success achieved 69%. In the second cycle obtained 80.2 with the number of success achieved 93%. This suggests that learning through the application type STAD cooperative learning model can be improved learning result.Key Words: Learning result, Students Teams Achievement Division (STAD)Model.